The Effect of Physical Activity on the Muscle Strength of Obese People' Backs - Wendra Wendra; Elly Noer Rochmah; Wisnu Fadhlurrohman (Poltekkes Kemenkes Palu, 2023)
In the last decade, the number of obese young adults has been increasing. Faculty of Medicine students tend to have low activity due to the busy learning schedule. Low activity is one of the risk factors for obesity and muscle strength, one of which is the back muscles that play a role in maintaining posture and supporting the body. This study aims to determine the level of physical activity and back muscle strength, as well as to examine the differences in back muscle strength between students at the Unjani Medical Faculty who suffer from obesity and low and high levels of physical activity. This study employs a cross-sectional design for its analysis. The ASAQ (Adolescent Sedentary Activity Questionnaire), the BMI (Body Mass Index) formula, and a back dynamometer are measuring instruments used to assess physical activity levels. Using a doctor's scale and a calibrated microtome, height and weight measurements were taken. To determine differences in muscle strength between study groups, the Mann-Whitney test (dk = 95%) was utilized. The results demonstrated that 33% of respondents had low levels of physical activity, with the majority of respondents being male (30.3%). As many as 28.1% of male respondents had low levels of back muscle strength and were inactive. There was a statistically significant difference (p 0.05) between the two groups in terms of back muscle strength, as determined by statistical tests. The results showed that obesity had an effect on reducing the back muscle strength of respondents.